The Critiques of Francis Schaeffer's Work - Niko Sudibjo (Polyglot, 2018)
This paper will attempt to discuss Francis Schaeffer’s life and thought, with special emphasis on his apologetics. The primary resource is one of his books, ‘How Should We Then Live?’ and also several books about Schaeffer from various other authors: (1) Francis Schaeffer’s Apologetics: A Critique by Thomas Morris, (2) Reflection on Francis Schaeffer, edited by Ronald W. Ruegsegger, and (3) Francis Schaeffer: The Man and His Message, written by Louis Gifford Parkhurst, Jr.  In his method of apologetical verification, he used of elements of common ground as a point of contact with unbelievers.  Unlike the inductive approach, he majors on inner, existential values as well as outer empirical data. In contrast with the pre-suppositional approach, Schaeffer’s method discovers and appeals to factual and personal data in confirmation of his hypothesis.BAHASA INDONESIA ABSTRAK: Tulisan ini mencoba untuk mendiskusikan kehidupan dan pemikiran Francis Schaeffer, terutama pada bidang apologetik. Bahan utama diskusi adalah berasal dari bukunya yang berjudul How Should we Then Live, dan juga pengarang-pengarang  lainnya yang membahas pemikiran Shaeffer dalam buku-bukunya antara lain: (1) Francis Schaeffer’s Apologetics: A Critique by Thomas Morris, (2) Reflection on Francis Schaeffer, edited by Ronald W. Ruegsegger, dan (3) Francis Schaeffer: The Man and His Message, written by Louis Gifford Parkhurst, Jr. Dalam metodenya verifikasi apologetik, Shaeffer menggunakan unsur-unsur kesamaan sebagai titik kontak dengan orang-orang yang belum mengenal Tuhan. Berbeda dengan pendekatan induktif, ia mengutamakan pada bagian dalam (inner) manusia, nilai-nilai eksistensial dan data-data empiris. Berbeda dengan pendekatan pre-suposisi, metode Schaeffer membuka  banyak  data  faktual dan personal yang mengonfirmasi hipotesisnya.